2011
DOI: 10.1245/s10434-010-1543-9
|View full text |Cite
|
Sign up to set email alerts
|

Do Perioperative Blood Transfusions Influence Prognosis of Gastric Cancer Patients? Analysis of 927 Patients and Interactions with Splenectomy

Abstract: Our study indicates a slightly, but not significantly, negative effect of allogeneic blood transfusion on prognosis of gastric cancer patients. In the subgroup of patients who underwent total gastrectomy, splenectomy seems to invert this mild effect, with a positive influence on overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…First, evidence indicates that excessive EBL may by itself impair immunity against cancer cells and nutritional status via loss of plasma constituents [8,27] . Further, patients' immunonutritional status plays an important role in tumor immunity [28] .…”
Section: Discussionmentioning
confidence: 99%
“…First, evidence indicates that excessive EBL may by itself impair immunity against cancer cells and nutritional status via loss of plasma constituents [8,27] . Further, patients' immunonutritional status plays an important role in tumor immunity [28] .…”
Section: Discussionmentioning
confidence: 99%
“…For the 2 studies, the indications for blood transfusions were different. One [23] was a multicenter study in Italy in which the indication for transfusion was a hemoglobin level of 8e10 g/dL or hemodynamically significant intraoperative blood loss. The indication in the other study [15] was intraoperative blood loss of >1000 mL or a hemoglobin level of <8 g/dL undertaken in a single center in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-regression analysis undertaken to explore explanations for tau 2 suggested that geographic area and tumor stage were not the significant sources of heterogeneity (Table 3). Using Galbraith plot, 2 studies [15,23] were found to be sources of heterogeneity (Fig. 4).…”
Section: Heterogeneity Test and Publication Bias For All-cause Mortalitymentioning
confidence: 99%
“…[12][13][14] Additionally, the interaction of splenectomy with transfusion in patients undergoing GAC resection has been debated. 9,10,12 The adverse effects of perioperative transfusion on patients undergoing curative resection of GAC and other malignancies have been hypothesized to be immune-mediated and perhaps dependent upon an intact spleen.…”
mentioning
confidence: 99%